Musculoskeletal Growth Modulation in Gilthead Sea Bream Juveniles Reared at High Water Temperature and Fed with Palm and Rapeseed Oils-Based Diets - Balbuena-Pecino, Sara (Animals (Basel), 2021)
SIMPLE SUMMARY: Diet optimization and global warming are two important challenges concerning fish farming. In the current study, both diets containing different vegetable oils (palm or rapeseed) and a situation of elevated water temperature (28 versus 21 °C) are evaluated in gilthead sea bream. The temperature increase caused a transcriptional modulation of development-related genes, while the palm and rapeseed oils-based diet appeared to be the most beneficial one, overall promoting an optimum endocrine environment for balanced musculoskeletal growth. Thus, data reveal the importance of considering diet formulation in a future climate change context to ensure sustainable production and welfare of aquatic animals. ABSTRACT: The upward trend of seawater temperature has encouraged improving the knowledge of its consequences on fish, considering also the development of diets including vegetable ingredients as an approach to achieve a more sustainable aquaculture. This study aims to determine the effects on musculoskeletal growth of: (1) a high-water temperature of 28 °C (versus 21 °C) in gilthead sea bream juveniles (Sparus aurata) fed with a diet rich in palm oil and, (2) feeding the fish reared at 28 °C with two other diets containing rapeseed oil or an equilibrated combination of both vegetable oils. Somatic parameters and mRNA levels of growth hormone-insulin-like growth factors (GH-IGFs) axis-, osteogenic-, myogenic-, lipid metabolism- and oxidative stress-related genes in vertebra bone and/or white muscle are analyzed. Overall, the data indicate that high-water rearing temperature in this species leads to different adjustments through modulating the gene expression of members of the GH-IGFs axis (down-regulating igf-1, its receptors, and binding proteins) and also, to bone turnover (reducing the resorption-activity genes cathepsin K (ctsk) and matrix metalloproteinase-9 (mmp9)) to achieve harmonic musculoskeletal growth. Moreover, the combination of palm and rapeseed oils seems to be the most beneficial at high-water rearing temperature for both balanced somatic growth and muscular fatty acid uptake and oxidation.